David Hume and the Science of Man - Parusniková, Zuzana (Teorie vědy / Theory of Science, 2011)
Hume built his philosophical system with the ambition to become a Newton of human nature. His science of man is the fulfillment of this project. Hume was inspired by the Newtonian experimental empirical method excluding hypotheses, and he applied this method to moral sciences; he took those to be the basis of all other knowledge. The observation of human cognitive faculties, however, brought him to sceptical conclusions concerning the rational justification of empirical sciences. His original ambitions are thus undermined and his scepticism leads to the loss of legitimacy of natural science. The core of Hume's science of man is twofold - it consists in the analysis of mind and of human social behaviour. Hume contributed to the development of psychology and helped to form social sciences as a specific research area. Following his empirical method based on observation, his science of man has rather a documentary role than any normative features.